"No topic is taboo": PETA's post-feminist pivot to human-centric imagery - Brown, Victoria L., author; Anderson, Karrin Vasby, advisor; Aoki, Eric, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2014)
In this thesis I argue that the People for the Ethical Treatment of Animals (PETA) perpetuate exclusionary and hurtful images in their "Boyfriend Went Vegan and Knocked the Bottom Out of Me" (BWVAKTBOOM) campaign. This campaign focuses on a young couple whose amorous activities leave the young woman, Jessica, with severe injuries. This campaign uses the manipulation of presence and absence to create controversy surrounding Jessica's agency. PETA uses this controversy to help forward a post-feminist ideology. This post-feminist message allows PETA to denigrate women to reassert masculine power and identity. I argue PETA chose to do this because of the "crisis of masculinity" that permeates popular media. The campaign reasserts masculine power through the reproduction of hypermasculinity, heteronormativity, and whiteness. The BWVAKTBOOM campaign reproduces hurtful, hegemonic images to reassert (vegan) masculine identity.
No topic is taboo: PETA's post-feminist pivot to human-centric imagery
Keywords: animal rights; PETA; media studies; BWVAKTBOOM